Spiritual leadership and organizational citizenship behavior: relationship with Confucian values. Issue 3 (2nd July 2016) - Hunsaker, William D.
Abstract: Spiritual leadership is achieving universal recognition as an effective tool to measure the interactive relationship between leaders, followers, and organizational performance. However, the construct needs robust investigation of the relationship to positive organizational behaviors in diverse country contexts. This study examined the relationship of spiritual leadership on organizational citizenship behavior (OCB) through the well-being of workers and the impact of Korean Confucian values with results fully supporting the relationship of employee well-being on OCBs. Furthermore, Confucian values, operationalized as Confucian mindset, also influenced and partially mediated the relationship between spiritual leadership and OCBs. The results of this study lend support to the enabling influence of spiritual leadership on positive organizational behavior such as OCB. Moreover, the study increases our understanding of the emic manifestations, like Confucian values, of leadership theory in generalizing western leadership theories to outside cultures.